The Impact Of Local Fried Chicken Attractiveness And Brand Prestige On Repurchase Intention Toward Western Fried Chicken Fast-Food Through Customer Satisfaction - Denzel Sudjono; Heriyadi Heriyadi; Bintoro Bagus Purmono; Wenny Pebrianti; Ahmadi Ahmadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the influence of Local Fried Chicken Attractiveness and Brand Prestige on Repurchase Intention toward Western fried chicken fast-food brands in Indonesia, with Customer Satisfaction acting as a mediating variable. A quantitative survey design was employed by collecting data from 200 Indonesian consumers who had experience consuming both local and Western fried chicken products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that the attractiveness of local fried chicken alternatives tends to reduce consumers’ satisfaction with Western fried chicken, while brand prestige positively enhances customer satisfaction and repurchase intention. Furthermore, customer satisfaction plays a crucial mediating role in translating brand perceptions and competitive attractiveness into repurchase intention. This research contributes to consumer behavior literature by extending Alternative Attractiveness Theory and Expectation–Confirmation Theory in the context of the Indonesian fast-food industry, particularly in explaining how competitive pressure from local brands and symbolic brand value influence consumers’ repurchase behavior.